The Legal Protection for Folk Songs from Unknown Origin: Orientation and Formulation in the Perspective of Legal Cybernetics - I Komang Gede Indrawan; I Gede Agus Kurniawan (SASI, 2023)
Introduction: The existence of the phenomenon of regional songs whose regional origins are unknown has led to legal problems in the form of a legal vacuum regarding legal protection. Existing laws and regulations are still missing in providing arrangements regarding regional songs whose regional origin is unknown.